Implementasi Pembelajaran Berbasis Nilai Islami dalam Meningkatkan Karakter Siswa di SD IT Al-Aufa Kota Bengkulu - Ire Ahdian Duri; Fiska Dela; Nadia Chendria Putri; Zanuba Nur Rahma; Dina putri Juni Astuti (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to describe the implementation of Islamic value-based learning in improving student character at Al-Aufa Islamic Elementary School in Bengkulu City. The focus of the study is directed at the strategy of integrating Islamic values ​​in the learning process, the habituation of worship and morals, teacher role models, and the religious school environment that forms an Islamic school culture. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of Islamic values ​​is carried out systematically through the integration of Islamic teachings into subjects, the habituation of daily worship, teacher role models, and the creation of a religious school environment. This implementation has been proven to have a significant impact on improving student character, especially in aspects of religiosity, discipline, responsibility, social awareness, and morals in interactions. These findings confirm that Islamic value-based learning has an important contribution in shaping the character of elementary school students comprehensively.